IN VIVO ANTIOXIDANT AND HEPATOPROTECTIVE EFFECTS OF HUGONIA MYSTAX IN PARACETAMOL INDUCED HEPATOTOXICITY IN RATS. - S SHIRODE, DEVENDRA; B JAIN, BRIJENDRA; KUMAR C B, MAHENDRA (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objectives: The objective of the present work is to study the in vivo anti-oxidant and hepatoprotective effects of Hugonia mystax in paracetamol (PCM) induced hepatotoxicity in rats. Methods: The in vivo anti-oxidant activity of 70% ethanol extract of leaves of H. mystax (HMEE) was assessed by determining the tissue glutathione and lipid peroxidation (LPO) levels. HMEE 200 and 400 mg/kg p.o. doses and silymarin p.o.100 mg/kg were administered to the PCM challenged rats. The effect of HMEE and silymarin on physical (liver weight and liver volume) and biochemical parameters (serum enzymes [serum glutamic oxaloacetic transaminase (SGOT) and serum glutamate-pyruvate transaminase (SGPT)], alkaline phosphate [ALP], and bilirubin) were measured. Furthermore, histopathological changes in the liver were studied. Results: The HMEE showed in the vivo anti-oxidant activity. Pre-treatment with HMEE for 7 days significantly reduced the elevated biochemical parameters (SGOT, SGPT, ALP, and bilirubin levels). The hepatic damage in animal pretreated with HMEE was minimal with distinct preservation of structures and architectural frame of the hepatic cells. Conclusion: These findings demonstrate the protective nature of HMEE against PCM Keywords: Hugonia mystax, Hepatoprotective, In vivo anti-oxidant, Paracetamol.